QUARK ANOMALOUS DIMENSIONS AT SMALL-X - Catani, S; Hautmann, F (1993)
We discuss the small-x behaviour of the parton anomalous dimensions in perturbative QCD beyond the leading logarithmic approximation. The flavour non-singlet anomalous dimensions are found to be regular at small x. The quark singlet anomalous dimensions are computed by resumming the perturbative series to all orders with next-to-leading logarithmic accuracy.